Investigations on peculiarities of land-water interface and its use as a stable testbed for accurately predicting changes in ecosystem responses to human perturbations: A sub-watershed scale study with the Ganga River. (15th May 2019) - Jaiswal, Deepa; Pandey, Jitendra
Abstract: In lotic systems, the hydrologic forcing together with structural and functional complexities make it difficult to predict how the river ecosystem will respond to human perturbations. We conducted two sets of studies selecting two segments; a 518 km main river stem, and two point source trajectories at the Ganga River during summer low flow of three consecutive years (2016–2018). The objective was to test if the land-water interface (LWI) of the river serves as a stable testbed for predicting human control on water quality and ecosystem responses. Samples were collected from LWI and complementary locations (50 m reach) from 8 selected sites of the main stem and 15 equidistant locations downstream each point source. Concentrations of carbon, nutrients and heavy metals at LWI varied in concordance with their concentrations in river water and riverbed sediment. Also, the microbial biomass (C, N, and P), activities and extracellular enzymes at LWI showed synchrony with their respective counterparts in riverbed sediment. We found strong positive correlations (p < 0.05-0.001) between these variables at LWI and their counterparts in water/riverbed sediment along the main stem and point source downstream. Our study establishes the credential of LWI for more accurately predicting changes in ecosystem responses to human perturbations. The study will facilitate accurate upscaling intercomparability across varied environmental control on the headwater streams-to-estuaries continuum. Graphical abstract: Image 1 Highlights: First report establishing land-water interface (LWI) as a predictor of ecosystem responses to human perturbations. LWI variables showed strong synchrony with their respective counterparts in river water and bed sediment. Microbial/enzyme activities at LWI provide mechanistic links with anthropogenic effect on river water and bed sediment. Heavy metals, if high in concentration, may mask site specific linkages. LWI showed strong riverine imprint at local as well as landscape scale.